Flux balance analysis and peptide mapping elucidate the impact of bioreactor pH on Chinese hamster ovary (CHO) cell metabolism and N-linked glycosylation in the fab and Fc regions of the produced IgG - Reddy J.V.; Singh S.K.; Leibiger T.; Lee K.H.; Ierapetritou M.; Papoutsakis E.T. (My University, 2025)
Culture conditions have a profound impact on therapeutic protein production and glycosylation, a critical therapeutic-quality attribute, especially for monoclonal antibodies (mAbs). While the critical culture parameter of pH has been known since the early 1990s to affect protein glycosylation and production, detailed glycan and metabolic characterization and mechanistic understanding are critically lacking. Here, Chinese Hamster Ovary (CHO) cells were grown in bioreactors at pH 6.75, 7, and 7.25 (± 0.03) to examine how pH affects cell metabolism and site-specific N-linked glycosylation of the produced broadly neutralizing anti-HIV IgG1 mAb. VRC01 has N-linked glycosylation sites in both the Fc region and the Fab region, a situation not previously examined with respect to mAb glycosylation as affected by culture conditions. Using parsimonious Flux Balance Analysis (pFBA) and Flux Variability Analysis (FVA), we dissect and quantitate the impact of pH on cell growth, glucose/lactate metabolism, accumulation of the toxic metabolite ammonia, IgG production rates, and nonessential amino acid metabolism. pFBA revealed that beyond the established mechanism of glutamine conversion to glutamate, ammonia is also produced by the reaction converting serine to pyruvate, especially in the later phases of culture. pFBA also provided insights into the switch from ammonia production to consumption, notably due to depletion of glutamine, and consumption of glutamate and aspartate. We document that culture duration and pH alter the complex bimodal patterns (production/uptake) of several essential and non-essential amino acids. Site-specific N-linked glycan analysis using glycopeptide mapping demonstrated that pH significantly affects the glycosylation profiles of the two IgG1 sites. Fc region glycans were completely fucosylated but did not contain any sialylation. The Fab region glycans were not completely fucosylated but contained sialylated glycans. Bioreactor pH affected both the fucosylation and sialylation indexes in the Fab region and the galactosylation index of the Fc region. However, fucosylation in the Fc region was unaffected thus demonstrating that the effect of pH on site-specific N-linked glycosylation is complex. © 2024